VD_FINDINFO Décision / 2015 / 508 vom 29. Juni 2015 - VD Tribunal cantonal (2015)
DÉTENTION POUR DES MOTIFS DE SÛRETÉ, RISQUE DE RÉCIDIVE, RISQUE DE FUITE | 221 CPP (CH), 229 al. 1 CPP (CH), 229 al. 3 let. b CPP (CH)